2015
DOI: 10.1016/j.sjpain.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design and reporting standards for improving the internal validity of pre-clinical studies in the field of pain: Consensus of the IMI-Europain consortium

Abstract: Background and aims Pain is a subjective experience, and as such, pre-clinical models of human pain are highly simplified representations of clinical features. These models are nevertheless critical for the delivery of novel analgesics for human pain, providing pharmacodynamic measurements of activity and, where possible, on-target confirmation of that activity. It has, however, been suggested that at least 50% of all pre-clinical data, independent of discipline, cannot be replicated. Additionally, the paucity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Of these, 62 publications were retained after full-text screening. We later identified two further duplicate publications of the same guidelines in different journals, giving a final list of 60 publications 5 7–65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 62 publications were retained after full-text screening. We later identified two further duplicate publications of the same guidelines in different journals, giving a final list of 60 publications 5 7–65…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the included publications (32) were narrative reviews that fell under the 1A category of our rating system (recommendations of individuals or small groups of individuals based on individual experience only, published stand-alone) 7 9 10 14 15 18 20 25 27 29 30 33 35 36 39 41–43 45 47–55 57 60 61 65. An additional 22 publications were consensus papers or proceedings of consensus meetings for journals or scientific or governmental organisations (category 1B) 3 4 8 12 13 17 19 24 26 28 32 34 37 38 44 46 56 59 62–64 66.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers increasingly recognize that most preclinical experiments do not represent a true preclinical efficacy study. In the past decades, discussions on the value of mouse models in predicting a therapy's efficacy for humans concluded that preclinical efficacy studies for therapies that aim at transition to clinical trials should be conducted with the same rigor as the clinical trials themselves (Conwit et al, 2011;Knopp et al, 2015). To help achieve high-quality preclinical studies, primary and secondary outcomes should be defined in advance and assessed according to standardized protocols, adequate control groups need to be chosen, and power analysis should be used to determine sample size; randomization and blinding need to be implemented, and a careful statistical analysis should be applied.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to declare what intervention effects are in the study protocol Inclusion/exclusion criteria Refers to criteria by which animals will be included or excluded in a given study, e.g. due to abnormal baselines or not reaching the required change in thresholds after designed experimental insult General principles to reduce experimental bias in each of the above-mentioned domains (Andrews et al 2016;Knopp et al 2015) are outlined in the following Table 3. Table 3 General principles to prevent experimental biases in hypothesis testing in vivo studies…”
Section: Major Domains General Descriptions Sample Size Estimationmentioning
confidence: 99%